2007
DOI: 10.1007/s00415-006-0349-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions in people with multiple sclerosis

Abstract: Thirty-three studies fulfilled the inclusion criteria; however, interventions varied widely in content, delivery and duration. Furthermore, failure to report full methodological details, as well as weaknesses in study design, reduced the strength of inferences that could be drawn from these studies. These notwithstanding, there were three studies of sufficient quality to provide some evidence regarding the value of education/information, goal setting, homework assignments, exercise, discussion forums and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 51 publications
(182 reference statements)
2
29
0
1
Order By: Relevance
“…The Oswestry Disability Index is a frequently used and well-studied tool found to be valid, reliable, and responsive, and its use as a standardized outcome measure to measure functional status has been advocated by numerous experts. [42][43][44] Quality of life or generic health and well-being could also be measured using one of the SF-36, SF-12, or EuroQoL. 44 Regardless of the outcome measures used, it is important for researchers to define primary end points, such as what distinguishes a clinically important improvement in back pain, disability due to back pain, quality of life, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The Oswestry Disability Index is a frequently used and well-studied tool found to be valid, reliable, and responsive, and its use as a standardized outcome measure to measure functional status has been advocated by numerous experts. [42][43][44] Quality of life or generic health and well-being could also be measured using one of the SF-36, SF-12, or EuroQoL. 44 Regardless of the outcome measures used, it is important for researchers to define primary end points, such as what distinguishes a clinically important improvement in back pain, disability due to back pain, quality of life, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Downs and Black (1998) stated that health care research must use a nonrandomized method and a checklist for non-RCT studies because current checklists lack detailed subscales and ignore the external validity of trials. Their checklist is now used for systematic reviews in rehabilitation (McCabe et al, 2007;Robbins, Houghton, Woodbury, & Brown, 2006;Teasell et al, 2007) and other fields (Hartling, Brison, Crumley, Klassen, & Pickett, 2004;Malcomson, Dunwoody, & Lowe-Strong, 2007). The Downs and Black checklist consists of 27 questions with four subscales: Reporting, External Validity, Bias, and Confounding.…”
Section: Methodological Quality Assessmentsmentioning
confidence: 99%
“…2,3,5,7 While offering hope that nonpharmacologic psychological or psychosocial interventions can improve health outcomes in MS, their effect may be due to the patient's placing an emphasis or developing dependence on the treatment (or therapist or group) rather than developing self-regulation or an internal locus of control.…”
Section: Methods Participantsmentioning
confidence: 99%
“…21 In that study, mean fatigue was ment, including evaluation of the effectiveness of group treatment with cognitive-behavioral therapy (CBT) 8 ; bibliotherapy, psychotherapy, and social discussion 5,7 ; mindfulness meditation 2 ; and individual stress-reduction therapy. 3 Each study found improvements across outcome measures such as disease progression, fatigue, quality of life, and depression.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation